PERBEDAAN HASIL PEMERIKSAAN TUBERCULOSIS PASIEN DM DAN NON DM MENGGUNAKAN SKALA IUATLD DI UPTD PUSKESMAS CITANGKIL KOTA CILEGON - Dwi Oktaviyaningsih; Ardy Prian Nirwana (LPPM Universitas Abdurrab, 2025)
Diabetes mellitus is a disease that is very dominant as a comorbid disease of pulmonary TB. People with DM have a weakened immune system so they are three times more likely to get active TB. TB patients who have been diagnosed with DM have a high risk of mortality during TB treatment and a risk of relapse after completing treatment. The aim of this study was to determine the difference in tuberculosis examination results in DM and non-DM patients using the IUATLD Scale. The research method was descriptive with a cross sectional approach with a sample size of 30 respondents divided into two, 15 respondents in the TB-DM group and 15 respondents in the TB Non-DM group. The sampling technique used was quota sampling. The data analysis techniques used are bivariate analysis. The results of univariate analysis showed that the majority of TB-DM sufferers were detected as positive for 3+ (46.7%) and the majority of non-DM TB sufferers were detected as positive for 1+ (53.3%). The results of bivariate analysis showed that statistically there was no difference in the results of tuberculosis examinations in TB-DM and non-DM TB patients using the IUATLD scale at the Citangkil Health Center, Cilegon City (p value: 0.301).